Using Smartphones for Work during Off-job Time and Burnout: Work-Life Conflict as a Mediator - Wongchompoo, Saharath (Journal for Strategy and Enterprise Competitiveness, 2022)
Smartphones are being increasingly used as a tool for work-related purposes in various organizations, including for work-related communication, completing work-related tasks, etc. However, smartphones are not used only during work hours, they are used for work during non-working time as well. This research aimed to examine the association between using smartphones for work during off-job time and the burnout of employees in the modern work society. In addition, the mediating effect of work-life conflict was also investigated. A total of 215 Thai employees participated through an online-based questionnaire survey by convenient random sampling. To collect data for analysis, the researcher used Hierarchical regression analysis by Program R. The results showed that using smartphones for work during off-job time was positively related to burnout ( = .137, p < .05), and positively related to perceived work-life conflict ( = .320, p < .001). Work-life conflict was positively related to burnout ( = .452, p < .001). Further, examining the mediating effect showed the significant mediating role of work-life conflict between using smartphones for work during off-job time and burnout. These results revealed the impact of using smartphones for work during off-job time on the important variables in organizations and highlighted an important issue for organizational management regarding the use of smartphones for work.